Pollen Grains Morphology of Angiosperms - Mallick, Pushpa Karna (International Journal of Applied Sciences and Biotechnology, 2020)
Pollen morphology of fourteen species of angiosperms from Kathmandu valley was investigated using aceto-carmine and palynological characters such as pollen size, shape, aperture numbers and exine sculpture were evaluated. The results indicate that various types of pollen grains are in angiosperms. In this investigation Pollen grains of Linum usitatissimum L. from the family Linaceae, Lathyrus odoratus L. from Fabaceae, Magnolia grandiflora L. from Magnoliaceae, Malva alcea L. and Malva sida L. from Malvaceae, Murraya koenigii Spreng from Rutaceae, Nerium oleander L. from Apocynaceae studied. Likewise, Ocimum tenuiflorum L., Salvia coccinea Buchz ex Etl. Salvia splendens Sellow ex J.A. Schultes from Lamiaceae, Oenothera rosea L. from Onagraceae, Prunus persica (L.) Batsch. from Rosaceae, Solanum nigrum L. from Solanaceae and Zinnia elegans L. from Asteraceae were studied in this investigation. Shape of the pollen grains found to be spheroidal, sub-spheroidal, elongate, oval, circular, ellipsoidal and triangular type. Ornamentation of exine wall found to be echinate, smooth, coarse, wrinkle and tected type. Aperture of the pollen grains found to be triporate to periporate. Sizes of the pollen grains encountered in this study were large, medium and small. The high diversity of exine ornamentation type in pollen grains of angiosperms has been associated to diversity in pollination systems. Echinate pollen grains train the bees to restrict to nectar collection and help the flowers to save more pollen grains for pollination. Smooth walled pollen grains are linked with wind or water pollination. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 205-210